Emulsion types, stability mechanisms and rheology: A review - Akbari, Sweeta; Nour, Abdurahman Hamid (International Journal of Innovative Research and Scientific Studies, 2018)
Emulsions have been widely used in different industrial processes. The development and production of good quality emulsions depend on the knowledge of emulsion preparation, stability mechanisms and rheological studies. To form stable emulsions, an emulsifier is required to reduce the droplet sizes of the emulsions and enhance the emulsion stability. The purpose of this review article is to provide information about types of emulsions, stability mechanisms and rheological studies as well as factor affecting the stability of emulsions.